Pendekatan kriminologi dan gender terhadap model kurikulum pembinaan narapidana anak kelas I Blitar - Saifullah Saifullah; Abdul Bashith; Mufidah Ch (State Institute of Islamic Studies (IAIN) Salatiga, 2019)
This study is aimed to elaborate the criminology and gender approaches taken to provide curriculum material contents in forming curriculum models for fostering child detainees in the child prison. Using legal and conceptual approaches, this study elaborates the findings as follows: in the criminology perspective, to provide curriculum material contents in forming curriculum models for fostering child detainees in child prison is by using religious approach, completing facilities and infrastructures, optimizing employee roles, applying formal education in prison, giving treatment and health care, supporting for the creation of social recovery, giving remission of crimes and assimilated opportunities including a leave to visit family or parole and a leave before being released. Whereas, in the gender perspective, it is by not distinguishing between sexes during the treatment to them. In addition, the final result of the curriculum model formation for fostering child detainees in child prison of LPKA (Child-specific Guidance Institution) in Blitar can be referred to as; the treatment system for correctional students in prison. This system consists of input in the form of an initial stage of 0 to 1/3 course with an administrative orientation pattern; the advanced stage consists of 1/3 to ½ course and ½ to 2/3 course; the final stage is 2/3 to any uncertain course stage with the achievement of correctional goal that is social reintegration: live, life, livelihood.